Karl Polanyi and the writing of The Great Transformation - Block, Fred (Theory & Society, 2003)
Karl Polanyi’s 1944 book, The Great Transformation , has been recognized as central for the field of economic sociology, but it has not been subject to the same theoretical scrutiny as other classic works in the field. This is a particular problem in that there are central tensions and complexities in Polanyi’s argument. This article suggests that these tensions can be understood as a consequence of Polanyi’s changing theoretical orientation. The basic outline of the book was developed in England in the late 1930s when Polanyi was working within a specific type of Marxist framework. However, as he was writing the book, he developed several new concepts, including fictitious commodities and the embedded economy, that led in new directions. Because circumstances did not give him the time to revise his manuscript, the book is marked by a tension between these different moments in his own theoretical development. The result is that Polanyi glimpses the concept of the always embedded market economy, but he does not name it or elaborate it.
Sociology
Keywords: Great Transformation; The (Book); capitalism; economics; sociology

Understanding the Diverging Trajectories of the United States and Western Europe: A Neo-Polanyian Analysis - Block, Fred (Politics & Society, 2007)
This article proposes a neo-Polanyian theoretical framework for understanding the dynamics within contemporary market societies. It uses this framework to analyze the divergence between the United States and other developed societies that has become more pronounced in the first years of the twenty-first century. The argument emphasizes the shifting political alliances of the business community in the United States and suggests that from 1994 onward, business lost power in the right-wing coalition to its religious Right allies. The growing power of a religious-based social movement is a critical ingredient in the unilateralist turn in the Bush Administration’s foreign policy.
Sociology
Keywords: U.S. business; economic sociology; embedded economy; embeddedness; social theory; varieties of capitalism

Crisis and renewal: the outlines of a twenty-first century new deal - Block, Fred (Socio-Economic Review, 2011)
Most analyses of the US financial crisis of 2007–2009 focus on the proximate causes. This article sees the crisis as a consequence of the decline of a long-term pattern of accumulation in the USA and seeks to outline the requirements for a new period of dynamic economic growth. Drawing on work done by the French Regulation theorists and the US analysts of Social Structures of Accumulation, the paper attempts to describe the types of institutional changes that would be needed to spark a new period of stable economic growth in the USA and in the rest of the world economy. The paper outlines what a green mass consumption economy might involve.
Sociology
Keywords: United States; capitalism; capitalist systems; crises; economic change; economic reform; financial crisis; green economy; institutional change

Varieties of What? Should We Still Be Using the Concept of Capitalism? - Block, Fred (Political Power & Social Theory, 2012)
This article argues that social scientists should reconsider the analytic value of the term "capitalism." The paper argues that the two most coherent definitions of capitalism are those derived from classical Marxism and from the Worm System theory of Immanuel Wallerstein. Marx and Engels' formulation was basically a genetic theory in which the structure of a mode of production is determined by the mode of surplus extraction. During the course of the 20th century, however, Marxist theorists had to modify this framework and the result has been an uncomfortable hybrid. Wallerstein resolved these tensions by redefining capitalism in terms of the logic of a worm system. However, his argument has difficulty in explaining the consequential variations over time in the specific rules and institutional structures that operate at the global level. The article goes on to argue in favor of Karl Polanyi's concept of market society because it focuses attention on the political governance of market societies at both the national and the global levels.
Sociology; Political Science
Keywords: Marxist philosophy; capitalism; mixed economy; political science; public administration; variational principles

Polanyian Themes: From Budapest to the Caribbean - Block, Fred (Development & Change, 2014)
KM: Book review of "From the Great Transformation to the Great Financialization"
Sociology
Keywords: FROM the Great Transformation to the Great Financialization (Book); From the Great Transformation to the Great Financialization (Book); LEVITT; Kari; 1923-; POLANYI LEVITT; Kari; economic development; nonfiction

A Neo-Polanyian Theory of Economic Crises - Block, Fred (American Journal of Economics and Sociology, 2015)
This article seeks to use Karl Polanyi's book, The Great Transformation, first published in 1944, to understand the global financial crisis that began in 2008. Polanyi's basic premise was that a great crisis must result from powerful causes. He argued that the crisis of the 1930s was a consequence of three distinct processes: deep imbalances in the global trading system, a crisis within the global financial mechanism that was supposed to manage those imbalances, and a failure of adaptation in the world's leading economy, the United States. The same processes can be seen at work in the last decade.
Sociology
Keywords: global financial crisis

Karl Polanyi and twenty-first century socialism - Block, Fred (openDemocracy, 2016)
Polanyi’s views were the exact opposite of his contemporary, Joseph Schumpeter, who famously defined democracy as giving people a choice over which elite group would rule over them.
Sociology
Keywords: socialism

The Return of Karl Polanyi - Somers, Margaret; Block, Fred (Dissent, 2014)
In the first half century of Dissent’s history, Karl Polanyi almost never made an appearance in the magazine’s pages. On one level this is surprising, because Polanyi was a presence in socialist circles in New York City from 1947 through the mid-1950s, the period of Dissent’s gestation. On another level it is unsurprising, in that Polanyi was a heterodox thinker—even among fellow socialists. With some significant exceptions, it has taken decades to recognize the extraordinary theoretical contributions to socialist thought that he made in his masterpiece, The Great Transformation: The Social and Political Origins of Our Time,first published in 1944.
Sociology
Keywords: Vienna (Austria); democracy; economics; primacy of politics; socialism

The Power of Market Fundamentalism - Block, Fred; Somers, Margaret R. (Harvard University Press, 2014)
What is it about free-market ideas that give them tenacious staying power in the face of such manifest failures as persistent unemployment, widening inequality, and the severe financial crises that have stressed Western economies over the past forty years? Fred Block and Margaret Somers extend the work of the great political economist Karl Polanyi to explain why these ideas have revived from disrepute in the wake of the Great Depression and World War II, to become the dominant economic ideology of our time.Polanyi contends that the free market championed by market liberals never actually existed. While markets are essential to enable individual choice, they cannot be self-regulating because they require ongoing state action. Furthermore, they cannot by themselves provide such necessities of social existence as education, health care, social and personal security, and the right to earn a livelihood. When these public goods are subjected to market principles, social life is threatened and major crises ensue.Despite these theoretical flaws, market principles are powerfully seductive because they promise to diminish the role of politics in civic and social life. Because politics entails coercion and unsatisfying compromises among groups with deep conflicts, the wish to narrow its scope is understandable. But like Marx's theory that communism will lead to a "withering away of the State," the ideology that free markets can replace government is just as utopian and dangerous.
Sociology; Political Science
Keywords: United States history; business & economics; economic history; economic policy; economic theory; free enterprise; political economy; political science; public policy; sociology

Karl Polanyi in an Age of Uncertainty - Block, Fred; Somers, Margaret R. (Contemporary Sociology, 2017)
Sociology
Keywords: DALE; Gareth; For a New West: Essays 1919-1958 (Book); Karl Polanyi: A Life on the Left (Book); POLANYI; Karl; 1886-1964; book review; nonfiction; socialism

Polanyi Symposium: a conversation on embeddedness - Krippner, Greta; Granovetter, Mark; Block, Fred; Biggart, Nicole; Beamish, Tom; Hsing, Youtien; Hart, Gillian; Arrighi, Giovanni; Mendell, Margie; Hall, John; Burawoy, Michael; Vogel, Steve; et al. (Socio-Economic Review (2004), 2004)
This conversation, transcribed from a conference in April 2002, is intended to illuminate current debates about the use and abuse of the embeddedness concept in economic sociology.
Sociology
Keywords: economic sociology; embeddedness; markets; symposium